Point Prevalence Survey of Antimicrobial Use among Hospitalized Patients in a Referral Hospital in Northwest Ethiopia: A Hospital-Based Cross-Sectional Study - Mengistie Yirsaw Gobezie; Minimize Hassen; Nuhamin Alemayehu Tesfaye; Mulat Belete Demessie; Tewodros Solomon; Ermiyas Alemayehu (International Journal of Clinical Practice)
Background. Globally, imprudent consumption practices contribute to the widespread threat of antimicrobial resistance (AMR). Standardized monitoring of antibiotic use is essential to combat AMR, yet few studies in sub-Saharan Africa, including Ethiopia, have utilized the World Health Organization (WHO) point-prevalence survey (PPS) methodology to examine antimicrobial use. Our setting lacks sufficient national data on this issue. This study aimed to examine the prevalence of antimicrobial use, common antimicrobial drug types, and indications for antimicrobial use in a major public hospital. Methodology. A cross-sectional PPS study design conducted in a hospital setting was utilized to explore the usage of antimicrobials in the adult wards of Felege Hiwot Comprehensive Specialized Hospital (FHCSH), employing the WHO-PPS methodology. The research was carried out between December 24th and 26th, 2022. All patients present in a hospital ward at 8 : 00 am on the designated survey day were included. Data were gathered through a combination of reviewing patients' medical records and conducting interviews with the attending physicians. Results. A total of 410 hospitalized patients were surveyed, out of which 258 (62.9%) patients were treated with at least one antimicrobial on the date of PPS. All antimicrobials were prescribed empirically. The most common indication for the therapeutic use of antimicrobials was community-acquired infections (166, 64.3%). The top three wards with a large number of antimicrobial prescriptions were the surgical (158, 42.5%), medical (144, 38.7%), and gynecology (55, 14.8%) wards. Ceftriaxone was the most frequently used antibiotic (35%) in all the wards. The mean number of antimicrobials prescribed to the patient was 1.44. Of the prescribed 372 antimicrobials, 60.1% belonged to the WHO watch group. Conclusion. Our findings indicate that a significant number of patients received at least one antimicrobial during the point-prevalence survey (PPS). Empirical prescriptions for community-acquired infections were prevalent. These results underscore the need for robust antimicrobial stewardship programs in Ethiopian hospitals.